Respuesta :

Answer:

D

Step-by-step explanation:

Find (f + g)(x) then evaluate (f + g)(9)

(f + g)(x) = f(x) + g(x)

= 4x - 1 + x² - 2 = x² + 4x - 3

Now substitute x = 9 into the expression

(f + g)(9) = 9² + 4(9) - 3 = 81 + 36 - 3 = 114 → D

Answer:

J.117

Step-by-step explanation:

f(x) =4x-1

if f(2)= 4(2)-1

f(2)= 8-1 = 7

f(2) = 7 equation 1

g(x) =x2-2

if g(4)= (4)2-2

g(4) = 8-2 = 6 equation 2

Now,

(f+g)(9) =?

subtitute equation 1 and 2

(7+6)(9)=?

(13)(9)=?

13×9= 117

Hence, the answer is 117

ACCESS MORE